Fitoremediasi In Vitro Logam Pb dan Cu Menggunakan Eceng Gondok (Eichhornia crassipes): Strategi Ramah Lingkungan dan Berkelanjutan - Siti Mahmudha; Fajar Nugraha; Muhammad Idris; Imas Masriah; Devi Lestari (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Heavy metal contamination, especially by lead (Pb) and copper (Cu), is a major environmental issue in aquatic ecosystems caused by industrial, mining, and agricultural activities. These metals are toxic, persistent, and bioaccumulative, posing risks to aquatic life and human health. Various remediation methods have been developed, including physical, chemical, and biological approaches; however, their effectiveness on a large scale remains limited. This study explores the potential of Eichhornia crassipes (water hyacinth) for in vitro phytoremediation of Pb and Cu. Plants were grown in Hoagland solution containing 100 mg/L of each metal. Metal accumulation in plant tissues was measured using Atomic Absorption Spectroscopy (AAS), and chlorophyll content was analyzed with a UV-Vis spectrophotometer. The results showed that Pb primarily accumulated in the roots, while Cu was more translocated to the leaves. Chlorophyll levels decreased more significantly in Cu-treated plants, indicating higher stress. These findings suggest that E. crassipes is a promising, cost-effective, and environmentally friendly option for the remediation of heavy metal-contaminated waters. The implementation of this technology could contribute to improving environmental quality and reducing the risk of heavy metal exposure to both ecosystems and human health.